Acute Limb Ischemia - Abdul Raziq Jamil; Soufni Morawati (Journal of Public Health Indonesian, 2025)
Acute Limb Ischemia (ALI) is a vascular emergency characterized by a sudden decrease in blood flow to the extremities, which can lead to amputation or death if not treated promptly. In Indonesia, epidemiological data on ALI is still limited, although cases are quite common, especially in patients with comorbidities such as diabetes mellitus and peripheral artery disease. This article aims to provide a comprehensive understanding of the pathophysiology, classification, diagnosis, and management of ALI, while highlighting the challenges of clinical practice in Indonesia, particularly in the context of limited facilities and the impact of the COVID-19 pandemic. This study uses a qualitative descriptive approach based on a literature review of relevant and verified scientific literature published between 2018 and 2024. The results show that the majority of ALI patients in Indonesia are men aged 49–56 years, with diabetes mellitus as the most common comorbidity. Typical clinical manifestations in the form of the “6Ps” and the Rutherford classification serve as important references in the diagnosis and determining therapeutic strategies. Primary management includes systemic heparinization and revascularization, both surgical and endovascular. The COVID-19 pandemic has exacerbated ALI through hypercoagulability, which increases the risk of thromboembolism. Therefore, early detection, increased diagnostic capacity, equitable access to vascular therapy, and healthcare professional education are key to reducing amputation and mortality rates due to ALI in Indonesia.